Tingkat Kesehatan Keuangan BUMN Konstruksi Tahun 2015-2021 - Indra Fajar; Mustanwir Zuhri (Sekolah Pascasarjana Perbanas Jakarta, 2023)
The focus of this paper is the description of financial soundness of construction SOEs which received assignments from the Government and/or carrying out tasks on National Strategic Projects (PSN). The study objects consist of PT Waskita Karya (Persero) Tbk, PT Wjaya Karya (Persero) Tbk. PT Adhi Karya (Persero) Tbk. PT Pembangunan Perumahan (Persero) Tbk, and PT Hutama Karya (Persero). The analysis performed by using the financial aspect assessment based on the Decree of the Minister of BUMN No. Kep-100/MBU/2002 concerning Assessment of the Healthiness Level of SOEs. The sample data used are the five construction SOEs with the period from 2015 to 2021. The results of this study indicate that the financial condition of the construction SOEs that receive Government assignments and/or work on PSN have variated conditions and generally experience a decline in the level of healthiness in 2020 and 2021. This declining of financial performance in line with the macroeconomy decline in conjunction with Covid-19 pandemic period.